AN ANALYSIS OF CONVERSATIONAL IMPLICATURE ON “JUMANJI: WELCOME TO THE JUNGLE” FILM - Saniatang, Saniatang; Sili, Surya; Setyowati, Ririn (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2020)
In this research, the researcher used the film as the object of the research entitled Jumanji: Welcome to the Jungle film and focused on understanding character utterances. The data were taken from the film script and scene in the form of utterances. Through the utterances, the participants tell their idea and opinion about something, but sometimes they do not say their goals directly; this is called implicature. Based on that, the researcher tries to understand the meaning of implicature utterances occurred in the film based on the implicature theory. This research was aimed at classifying the types of conversational implicature, which have been done by the five main characters in the film and then explaining the implied meaning. The researcher used Levinson's implicature theory and context by DeVito. The data were explained by showing the maxim flouted by the main characters, the context of the situation, the types of conversational implicature, and the implied meaning of the utterances. Dealing with the purposes of the research, it was found that the five main characters used implicature. Thirty-seven utterances contained conversational implicatures, which comprise thirty-four particularized conversational implicature, and three generalized conversational implicature. The five main characters used particularized conversational implicature more frequently than generalized conversational implicature. In addition, it was also found that the implied meaning behind main characters’ utterances mostly depend on the context of the conversation. The implied meaning found were informing, complaining, refusing, reminding, criticizing, assuring, affirming, apologizing, and entreating.